La curva de rendimiento y su relación con la actividad económica: Una aplicación para México - Mario Reyna Cerecero; Diana Salazar Cavazos; Héctor Salgado Banda (Banco de México, 2008)
– There are a significant number of papers that show that the slope of the yield curve has a certain ability to forecast real economic activity and inflation. However, in emerging economies this source of information has not been thoroughly used; Mexico is not an exception. The economic stability achieved in this country in recent years has allowed the government to issue, since 2001, long-term bonds. With more stable economic cycles, the information included in the long part of the yield curve could be a useful tool to estimate future economic activity. This document analyses the predictive power of the spread. Moreover, the spread is divided into two main components to analyse the origin of its predictive power. Next, the power of the spread to forecast economic cycles is tested. Last, out-of-sample tests of the spread are carried out. The findings show that the yield curve provides significant information about future economic activity.
Keywords: C5; E44; E52; F37; 330; Yield curve; forecasting; economic activity